2016
DOI: 10.1016/j.neubiorev.2015.12.014
|View full text |Cite
|
Sign up to set email alerts
|

GABA-ergic cell therapy for epilepsy: Advances, limitations and challenges

Abstract: Diminution in the number of gamma-amino butyric acid positive (GABA-ergic) interneurons and their axon terminals, and/or alterations in functional inhibition are conspicuous brain alterations believed to contribute to the persistence of seizures in acquired epilepsies such as temporal lobe epilepsy. This has steered a perception that replacement of lost GABA-ergic interneurons would improve inhibitory synaptic neurotransmission in the epileptic brain region and thereby reduce the occurrence of seizures. Indeed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
89
1
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(95 citation statements)
references
References 88 publications
1
89
1
4
Order By: Relevance
“…Although it has been suggested that seizure suppressive effects of MGE progenitor cell transplantation may be transient 18,25 , here starting at 180 DAT, and in our earlier publications at 45 and 60 DAT 14,17 we have found absolutely no evidence to support this conclusion. There are at least two potential explanations for this discrepancy.…”
Section: Discussioncontrasting
confidence: 90%
See 1 more Smart Citation
“…Although it has been suggested that seizure suppressive effects of MGE progenitor cell transplantation may be transient 18,25 , here starting at 180 DAT, and in our earlier publications at 45 and 60 DAT 14,17 we have found absolutely no evidence to support this conclusion. There are at least two potential explanations for this discrepancy.…”
Section: Discussioncontrasting
confidence: 90%
“…Using a well-characterized pilocarpine model of acquired epilepsy, we also demonstrated that MGE progenitors transplanted into adult hippocampus reduced unprovoked seizures by 90% starting at 60 DAT 14 . While our studies strongly support continued preclinical development of MGE progenitor transplantation as a therapy for intractable epilepsies, other groups suggested these effects may be transient 18,24,25 and CGE-based cell transplantation for epilepsy has not been studied.…”
Section: Introductionsupporting
confidence: 52%
“…23,24) On the other hand, dysfunction in neurotransmission mediated by the inhibitory neurotransmitter GABA is related to the onset and development of several neurological disorders including epilepsy and insomnia. 25,26) The high-affinity transporters for glutamic acid and GABA are EAAT and GAT, respectively, but the low-affinity transporters are unclear. Glutamic acid and GABA are amino acids and zwitterionic compounds.…”
Section: Physiological Roles Of Organic Cation Transporters In Neuronsmentioning
confidence: 99%
“…Exploring these complex avenues will undoubtedly advance design of effective preventative strategies for a number of common, debilitating conditions. Furthermore, technical advances fueled by understanding of cIN development are quickly making cell culture and grafting therapies imaginable treatments for these devastating disorders 166,167 .…”
Section: Discussionmentioning
confidence: 99%